Lesson plan proposal: using background knowledge and previous structure knowledge for a timed-writing activity as a result of reading and pre-reading sequences - Rafael Santos Raspanti (Ministerio de Educación, Dirección General de Educación Superior, 2018)
The interplay between the receptive macro skill reading and the corresponding productive one (writing) has been the object of study of an array of scholars willing to describe and seize EFL/ESL teaching and learning. This project proposes a reading/writing class in a second year chair (Discursive Practices II) in an English teaching training tertiary school in Villa del Totoral, Córdoba Province. This class involves the completion of a narrative paragraph taking into account top-down and bottom-up processing.